The factors impact to exchange rate in middle income countries / Nur Hanani Aqilla Hairuddin and Nurul Hidayah Rosli - Hairuddin, Nur Hanani Aqilla; Rosli, Nurul Hidayah (Faculty of Business and Management, 2018)
Most of analyst, economist and researchers want to know the factors that impact to exchange rate. This topic is important to economic country. So in this study focus on factors that impact to exchange rate in middle income countries. The chosen micro variables are consumer price index (CPI), export (EXPO), foreign direct investment (FDI), import (IMPO), gross domestic product (GDP), salary or wages (SAWA), and unemployment rate (UNEM) as major determine factors. The study is confined to the period of 10 years over 2008-2017 in Malaysia, Colombia, Mexico, Brazil, South Africa, Pakistan, Philippine, China, Georgia and Zambia. Those countries are middle income countries. The sources of data are from world bank data and secondary data from many previous researches. In this study using normality test, correlation test and regression test. In normality test, there have significant evidence using Levin, Lin and Shin Test. For empirical analysis after checking the data for regression method has been uses, the result found that export, import, salary and wages are significant to exchange rate while others variables are insignificant.